Elucidating the role of shape anisotropy in faceted magnetic nanoparticles using biogenic magnetosomes as a model. Issue 30 (2nd July 2020) - Gandia, David; Gandarias, Lucía; Marcano, Lourdes; Orue, Iñaki; Gil-Cartón, David; Alonso, Javier; García-Arribas, Alfredo; Muela, Alicia; Fdez-Gubieda, Mª Luisa
Abstract : A model based on finite element techniques has been developed to calculate the shape-anisotropy energy of magnetic nanoparticles. Abstract : Shape anisotropy is of primary importance to understand the magnetic behavior of nanoparticles, but a rigorous analysis in polyhedral morphologies is missing. In this work, a model based on finite element techniques has been developed to calculate the shape anisotropy energy landscape for cubic, octahedral, and truncated-octahedral morphologies. In all cases, a cubic shape anisotropy is found that evolves to quasi-uniaxial anisotropy when the nanoparticle is elongated ≥2%. This model is tested on magnetosomes, ∼45 nm truncated octahedral magnetite nanoparticles forming a chain inside Magnetospirillum gryphiswaldense MSR-1 bacteria. This chain presents a slightly bent helical configuration due to a 20° tilting of the magnetic moment of each magnetosome out of chain axis. Electron cryotomography images reveal that these magnetosomes are not ideal truncated-octahedrons but present ≈7.5% extrusion of one of the {001} square faces and ≈10% extrusion of an adjacent {111} hexagonal face. Our model shows that this deformation gives rise to a quasi-uniaxial shape anisotropy, a result of the combination of a uniaxial ( K sh–u = 7 kJ m −3 ) and a cubic ( K sh–c = 1.5 kJ m −3 ) contribution, which is responsible for the 20° tilting of the magnetic moment. Finally, our results have allowed us to accurately reproduce, within the framework of the Landau–Lifshitz–Gilbert model, the experimental AC loops measured for these magnetotactic bacteria.